The Role of Islamic Cleric Leadership in Improving the Quality of Traditional Islamic School Education - Indah Pala Sari; Ismawati, Ismawati; Aprina, Siti Citra Aulia (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2024)
This study aims to analyze the strategic role of the kiai as the leader of Islamic boarding schools (pondok pesantren) in building a pesantren culture that contributes to the formation of institutional character. This institutional character serves as the identity of the organization, reflecting the process of developing institutional excellence through the growth of scholarly traditions and a clear system of educational management. The research employs a qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through organizing and classifying data, as well as verifying its validity using triangulation and referencing scholarly materials. The findings of the study reveal that the kiai plays a pivotal role in improving the quality of education in Islamic boarding schools through various strategies. These include strengthening an integrated curriculum combining religious and general subjects, enhancing teacher quality through training and recruitment of qualified educators, improving facilities and infrastructure, implementing active learning approaches, conducting continuous evaluation and monitoring, and developing extracurricular activities aligned with students' interests and talents. Furthermore, the kiai fosters collaboration with parents and the community to support educational programs holistically and sustainably. The implications of this research highlight that the responsibilities of the kiai extend beyond administrative tasks to include providing spiritual and moral guidance to students, creating a conducive learning environment, instilling Islamic values, and preparing students to become individuals with noble character who are ready to face life's challenges. Therefore, the role of the kiai is crucial in shaping Islamic boarding schools as excellent and competitive educational institutions.